Characterization of genomic, physiological, and probiotic features Lactiplantibacillus plantarum DY46 strain isolated from traditional lactic acid fermented shalgam beverage - Yetiman, Ahmet E.; Keskin, Abdullah; Darendeli, Busra Nur; Kotil, Seyfullah Enes; Ortakci, Fatih; Dogan, Mahmut (ELSEVIER, 2022)
Lactiplantibacillus plantarum is a significant probiotic where it could be found in ubiquitous niches. In this study, a new Lb. plantarum strain DY46 was isolated from a traditional lactic-acid-fermented beverage called shalgam. The whole genome of the DY46 was sequenced and obtained sequences were assembled into a 3.32 Mb draft genome using PATRIC (3.6.8.). The DY46 genome consists of a single circular chromosome of 3,332,827 bp that is predicted to carry 3219 genes, including 61 tRNA genes, 2 rRNA operons. The genome has a GC content of 44.3% includes 98 predicted pseudogenes, 25 complete or partial transposases and 3 intact prophages. The genes encoding enzymes related in the intact EMP (Embden-Meyerhof-Parnas) and PK (phosphoketolase) pathways were predicted using BlastKOALA which is an indicator of having facultative heterofermentative pathways. DY46 genome also predicted to carry genes of Pln E, Pln F and Pln K showing the antimicrobial potential of this bacterium which can be linked to in vitro antagonism tests that DY46 can inhibit S.enterica sv. Typhimurium ATCC14028, K. pneumonie ATCC13883, and P. vulgaris ATCC8427. Moreover, it is determined that all resistome found in its genome were intrinsically originated and the strain was found to be tolerant to acid and bile concentrations by mimicking human gastrointestinal conditions. In conclusion, L. plantarum DY46 is a promising bacterium that appears to have certain probiotic properties, confirmed by in vitro and in silico analyses, and is a potential dietary supplement candidate that may provide functional benefits to the host.
Keywords: Shalgam; Lactiplantibacillus plantarum; Probiotic; Genome; Carbohydrate fermentation patterns; LACTOBACILLUS-PLANTARUM; ANTIBIOTIC-RESISTANCE; BACTERIA; FOOD; SEQUENCE; TOOLS; DIVERSITY; ADHESION; GROWTH; SAFETY; Food Science & Technology